3‐Bromoacetylcoumarin, a Crucial Key for Facial Synthesis of Biological Active Compounds. Issue 24 (21st June 2022) - Hosseini Nasab, Narges; Azimian, Fereshteh; Kruger, Hendrik G.; Kim, Song Ja
Abstract: Compounds containing the coumarin scaffold are widely used in the pharmaceutical and medicinal industries. The biological activities of coumarin containing derivatives make the attractive for the develop new drugs. Different methods and techniques are developed to synthesize new drugs using coumarin as a starting material. This review summarized various methods, techniques and reaction conditions for synthesis of coumarins containing compounds from 3‐bromoacetylcoumarin. A total of 79 coumarin intermediates and products are reported herein. The different reactions include nucleophilic substitutions, one‐pot and multi‐step synthesis for preparation of coumarin containing compounds through different mechanisms and the outcomes achieved through such reactions are discussed. The prepared compounds showed a range of activities resulting in antifungal, antimicrobial, anti‐inflammatory, antidiabetic and cholinesterase inhibitors. The nucleophilic substitution reactions involving urea related compounds, followed by intramolecular cyclization lead to imidazole and thiazole moieties, which exhibit antibacterial activities. It is hoped that this review provides useful insight for researchers engaged in this field to expand the knowledge gained in this area. Abstract : In the pharmaceutical and medicinal industries, compounds containing the coumarin scaffold are frequently utilized. Coumarin‐containing derivatives have biological properties that make them appealing for therapeutic development. The numerous methods, techniques, and reaction conditions for the synthesis of coumarins containing compounds from 3‐bromoacetylcoumarin were summarized in this review. Antifungal, antibacterial, anti‐inflammatory, antidiabetic, anticancer, and cholinesterase inhibitor properties have been demonstrated in these compounds.